Gastric sleeve and laparoscopic parietal repair - Giroff, Nicolás; Bentancur, Martín; Valsangiacomo, Pablo; González, Daniel (Cirugía del Uruguay, 2020)
Introduction Ventral hernia management in patients undergoing surgery bari átrica is controversial, not there is consensus in the literature current about the optimal time of hernia repair in relationship to the procedure baric, as well as the choice of the repair method hernial. Every bariatric patient with a defect of the abdominal wall should be addressed individually, taking into account account for factors such as the presence of symptoms, size of the parietal defect and hernia reductibility. Description of contents In the video it exposes the realization of a laparoscopic gastric sleeve in a patient morbidly obese with a recurrence of an umbilical hernioplasty. In the same act it takes Perform parietal repair laparoscopically, highlighting the closure of the defect with extracorporeal stitches, ending with the intra-abdominal placement of a Composite mesh (polyester / collagen) with an overflap of 5cm.